Exercise-induced changes of left ventricular diastolic function in postmenopausal amateur marathon runners: assessment by echocardiography and cardiac biomarkers. (June 2014) - Knebel, Fabian; Spethmann, Sebastian; Schattke, Sebastian; Dreger, Henryk; Schroeckh, Sabrina; Schimke, Ingolf; Hättasch, Robert; Makauskiene, Rita; Kleczka, Josephine; Sanad, Wasiem; Lock, Jürgen; Brechtel, Lars; et al.
Purpose: Diastolic dysfunction is common among elderly women. Recently, concerns regarding marathon-induced myocardial damage were raised among young male runners. The goal of our study was to assess the impact of marathon running on systolic and diastolic ventricular function before and immediately after completing a marathon among postmenopausal well-trained amateur women. Methods: A total of 89 female runners of the Berlin Marathon were included (35 postmenopausal and 54 premenopausal female controls) and examined before, immediately, and 2 weeks after the race by echocardiography (including tissue Doppler- and 2D strain speckle tracking) and underwent blood tests. Results: After the marathon, there was a significant increase in E/E′ (postmenopausal 8.5 ± 2.3 vs. 10.9 ± 3.2 post race; control: 8.1 ± 1.8 vs. 9.9 ± 2.9 post race, p < 0.001) and a decrease in E/A in both groups (postmenopausal 1.3 ± 0.36 vs. 0.9 ± 0.21 post race; control 1.7 ± 0.6 vs. 1.1 ± 0.3; p < 0.001). In contrast, regardless of the hormonal status the atrial contraction increased significantly. Left and right ventricular systolic contractility, as assessed by speckle tracking and pulsed-wave tissue Doppler velocities, showed a significant increase in both groups. Of all runners, 55 (61.8%) experienced increases in troponin T and/or N-terminal-B-type natriuretic peptide after the race. All echocardiographic and laboratory parameters returned to normal within 2 weeks. Conclusions: 2D strain analysis of the left and right ventricles showed an acute improvement of the systolic function after marathon running in pre- and postmenopausal well-trained women. There were no long lasting detrimental effects on the diastolic function.